PERAN BUDAYA PATERNALISTIK DAN KOMITMEN ORGANISASI DALAM MEMODERASI PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN MOTIVASI KERJA PADA KINERJA MANAJERIAL - Lestariani, Dewi; Sukartha, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
This study is aimed to determine the role of paternalistic culture and organizational commitment in moderating  budgetary participation influence and working motivation in manajerial performance. The method used is the documentation and survey methods, using a structured questionnaire technique which is  addressed to the Head of Unit, Head of the Regional Working Unit, Head of Administration, Head of Section, Commitment Officer, Treasurer and Assistant. The technique  of  the population sampling is based on a certain criteria (purposive sampling). The data analysis technique which is used is multiple linear regression and Moderated Regression Analysis (MRA). The results of the research showed that: the budgeting participation influences the managerial performance, The working motivation influences the managerial performance, The paternalistic culture is not able to moderate the  budgetary participation  influence in managerial performance, The paternalistic culture is able to moderate the working motivation influence in managerial performance, The organizational commitment is able to moderate the  budgetary participation influence in Managerial Performance, The organizational commitment is not able to moderate the working motivation  influence in Managerial Performance.
Keywords: budgetary participation, working motivation, paternalistic culture, organizational commitment and managerial performance